2002
DOI: 10.1590/s1413-86702002000400003
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of undetectable plasma viral load in HIV-positive adults receiving antiretroviral therapy in Southern Brazil

Abstract: Factors associated with undetectable viral load (<80 copies/ml) were investigated among non-pregnant adults in antiretroviral treatment in a specialized service for HIV/AIDS in Southern Brazil. Use of antiretrovirals was investigated in two interviews (one month interval). Clinical data were collected from the clinical records; viral load previous to adherence measurement was defined the viral load previous to the first interview; the final viral load, the viral load subsequent to the second interview (interva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
16
0
4

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 29 publications
2
16
0
4
Order By: Relevance
“…Data from the literature suggest that, on the one hand, alcohol or illicit drug abuse and psychiatric comorbidities are associated with low adherence to highly active antiretroviral therapy, 14 whereas on the other hand, viral load below the limit of detection 35 is a predictor of adherence. Moreover, a study of 4,989 outpatients conducted at five American hospitals observed that patients with six or more annual psychiatric visits had fewer episodes of ARV discontinuation (OR = 0.57, 95%CI 0.47-0.69) compared to those not receiving psychiatric treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Data from the literature suggest that, on the one hand, alcohol or illicit drug abuse and psychiatric comorbidities are associated with low adherence to highly active antiretroviral therapy, 14 whereas on the other hand, viral load below the limit of detection 35 is a predictor of adherence. Moreover, a study of 4,989 outpatients conducted at five American hospitals observed that patients with six or more annual psychiatric visits had fewer episodes of ARV discontinuation (OR = 0.57, 95%CI 0.47-0.69) compared to those not receiving psychiatric treatment.…”
Section: Discussionmentioning
confidence: 99%
“…These authors accompanied patients naïve to cART for six years, and found that only 27.5% remained with levels below the limit of detection after one year of treatment with triple drug schemes, composed of both NNRTI and PI. For SILVEIRA et al 36 and CUÉLLAR…”
mentioning
confidence: 98%
“…, an undetectable level as well as its maintenance for the longest possible period of time is associated with factors of compliance or non-compliance to treatment 7,36 such as education level, socioeconomic factors, side effects, the number of doses of medicaments and the evolution of clinical parameters 07 . Some authors 10,16 hypothesized that patient age, HIV-1 disease stage before cART initiation, immunological and virological responses to cART in the first five years of treatment and types of cART regimens would significantly affect later CD4+ count and RNA levels among long-term cART users.…”
mentioning
confidence: 99%
“…The base document of the United Nations General Assembly Special Session on HIV/AIDS (UNGASS) defines targets for Science, Technology and Innovation relating to HIV/AIDS in its items [70][71][72][73]. The present text analyses some of the main items in this section, giving emphasis to core questions in public health, rather than to its interfaces with broader markers for action within civil society, for formulation and implementation of public policies and for industrial policy strategies.…”
Section: Introductionmentioning
confidence: 99%